F(x) = x² + 4x + 10
f(x) - 10 = x² + 4x
perfect square:
x² + 4x + 4 ⇒ (x + 2)²
(x + 2)² = x(x+2) + 2(x+2) = x² + 2x + 2x + 4 = x² + 4x + 4
f(x) - 10 + 4 = x² + 4x + 4
f(x) - 6 = (x+2)²
f(x) = (x+2)² + 6
So far your getting all of them right. But, maybe next time upload a better picture because it’s hard to see what you wrote.
The relevant formula that we can use in this situation is:
v = v0 + at
where v is the final velocity, v0 is the initial velocity
= 20 km/hr, a is acceleration at 3.4 m/s^2 and t is time at 20 seconds
First convert v0 to m/s, v0 = 5.56 m/s
v = 5.56 m/s + 3.4 m/s^2 * 20 s
v = 73.56 m/s
Then convert back to km/hr:
<span>v = 264.82 km/hr</span>
Answer:
1:2
Step-by-step explanation:
6:9 can be simplified to
divide by 3 to get simplest form
1:2
The answer would be (8/11,0) as the x-intercept